2022
DOI: 10.1186/s12883-022-02568-7
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 6 infection as a trigger of multiple sclerosis: an update of recent literature

Abstract: Background This is an update on the existing evidence regarding a relationship between infection with human herpesvirus 6 (HHV-6) and multiple sclerosis (MS) in order to contribute on the attempt to define the nature and strength of that relationship. Results Study quality was assessed using the criteria proposed by Moore and Wolfson and by the classification criteria used by the Canadian Task Force on the Periodic Health Examination. Studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Our data confirms the potential link between herpesvirus infection and MS. We found significant association between HHV6 seropositivity and diagnosis of MS. This data corroborates previous observations where HHV6 infection was linked to MS ( 29 , 65 67 ). Interestingly, EBV was also identified as a risk factor for MS ( 19 , 24 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data confirms the potential link between herpesvirus infection and MS. We found significant association between HHV6 seropositivity and diagnosis of MS. This data corroborates previous observations where HHV6 infection was linked to MS ( 29 , 65 67 ). Interestingly, EBV was also identified as a risk factor for MS ( 19 , 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…In conclusion, we have found an association between HHV6 sero-positivity and MS diagnosis. This data contributes to our understanding the role of herpesvirus infection as risk factor of MS. Two viruses, EBV and HHV6, are frequently associated with MS ( 24 , 67 , 113 , 114 ). Also, childhood herpesvirus infection increases the risk of MS diagnosis ( 115 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another herpesvirus, Human Herpesvirus 6 (HHV-6) is widely spread in the population and has also been associated with neuroimmunologic disorders, including MS ( 101 ). Animal and in vitro models have demonstrated that CD46, a complement regulator involved in complement inhibition, is a receptor for the HHV-6 ( 102 , 103 ).…”
Section: Ebv Hhv-6 and Ms: Further Suggestion Of A Potential Critical...mentioning
confidence: 99%
“…The growing evidence of a possible virus-triggered origin of MS brought up models of virus-induced demyelination to explore its potential etiology [34][35][36]. Usually, mice are infected with Theiler's murine encephalomyelitis (TMEV) or murine hepatitis (MHV) viruses.…”
Section: Viral-induced Modelsmentioning
confidence: 99%